Long-Term Supplementation of Microencapsulated ursodeoxycholic Acid Prevents Hypertension in a Mouse Model of Insulin Resistance: - Al-Salami, Hani; Mamo, John; Mooranian, Armin; Negrulj, Rebecca; Lam, Virginie; Elahy, Mina; Takechi, Ryu (MVS Medizinverlage Stuttgart, 2016)
Copyright © 2016. Georg Thieme Verlag KG. All rights reserved. Hypertension is a significant comorbidity associated with insulin resistance and type-2 diabetes. Limited evidence show that ursodeoxycholic acid (UDCA) has some anti-hypertensive effects. However, the potential effect of UDCA on hypertension induced by type-2 diabetic insulin resistance has not been reported. In C57Bl6 wild-type mice, insulin resistance was induced by the chronic ingestion of diet enriched in fat and fructose (HFF). HFF mice were randomized to treatment with UDCA or candersartan incorporated into the diet to achieve an ingested dose of approximately 70 mg/kg/day of UDCA or 3 mg/kg/day respectively. Systolic and diastolic blood pressure were measured with tail-cuff method. At 4 weeks of dietary treatment systolic and diastolic blood pressure were comparable in HFF and low-fat (LF) control mice. Co-administration of candesartan at 4 weeks significantly decreased systolic and diastolic blood pressure, UDCA showed no anti-hypertensive effect at 4 weeks. At 24 weeks of dietary intervention, HFF fed mice had substantially elevated systolic blood pressure compared to LF controls. The provision of UDCA substantially attenuated the dietary HFF induced increase in systolic blood pressure concomitant with significantly lower plasma angiotensin II. The anti-hypertensive effect of UDCA in HFF mice was comparable to candesartan. The data suggests that long term supplementation of UDCA effectively lowers hypertension in a dietary induced model of type-2 diabetic insulin resistance.